APPROACHES TO THE CHOICE OF BIOPREPARATIONS IN THE CORRECTION OF INTESTINAL DYSBACTERIOSIS IN CHILLDREN WITH CHRONIC HEPATITIS B ASSOCIATED WITH LAMBLIASIS - F. I. Inoyatova; N. F. Nurmatova; D. M. Mirzamukhamedov (LLC "Diagnostics and Vaccines", 2015)
The developed technique of "loading" test in vitro was used for choice of biological agent for correction of the intestinal dysbacteriosis (ID) in 75 children with chronic hepatitis B (CHB) associated with lambliasis. There was established direct proportional decrease in ability of lymphocytes to E-rosette forming in dependence on severity degree of intestinal dysbacteriosis. Bifilax-immuno (62.7%) appeared to be most sensitive biological agent in the test in vitro which was differed by qualitative and quantitative contents in comparison with Lacto-G (48.0%) and Narimax-plus (38.7%), , p<0,05. The evaluation of the efficacy of the directed therapy allowed increase in efficacy of the treatment by 40.1%. Development of clinical, biochemical and microbiological remission was achieved in 76.5%, 64.4% and 62.0% respectively. In this connection the children with chronic hepatitis B associated with lambliasis were recommended to examine intestinal microflora and to use test in vitro before choice of biological agents for effective correction of the intestinal dysbacteriosis taking onto account body individual sensitivity.